2000
DOI: 10.1002/1521-3773(20001016)39:20<3669::aid-anie3669>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel Group-Transfer Three-Component Coupling of Silyltellurides, Carbonyl Compounds, and Isocyanides

Abstract: A new thermal coupling reaction forms silyloxy imidoyl tellurides 2 from silyl tellurides 1, carbonyl compounds, and phenyl isocyanide [Eq. (1)]. A mechanism that involves the generation of the silyl radical from the silyl telluride and subsequent chemoselective coupling with carbonyl compounds and the isocyanide is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In contrast, TEMPO had a negligible impact on reactions employing TES ( 1b ) and TIPS ( 1c ), even when present at much higher concentrations (80 mM TEMPO); the origins of this profound difference in behavior is discussed later. Nonetheless, further tests for discrete radical intermediates , were conclusively negative: 4-F-benzophenone ( 12 ) exclusively underwent 1,2-addition (Scheme , B), , cyclopropyl ketones ( 6/7 ) reacted without any trace of competing ring-opening (Scheme , C), and competition between ketone 2 and 4-biphenyl methyl ketone for limiting TMSCF 3 ( 1a ) favored 2 ( k rel = 1.93) …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, TEMPO had a negligible impact on reactions employing TES ( 1b ) and TIPS ( 1c ), even when present at much higher concentrations (80 mM TEMPO); the origins of this profound difference in behavior is discussed later. Nonetheless, further tests for discrete radical intermediates , were conclusively negative: 4-F-benzophenone ( 12 ) exclusively underwent 1,2-addition (Scheme , B), , cyclopropyl ketones ( 6/7 ) reacted without any trace of competing ring-opening (Scheme , C), and competition between ketone 2 and 4-biphenyl methyl ketone for limiting TMSCF 3 ( 1a ) favored 2 ( k rel = 1.93) …”
Section: Resultsmentioning
confidence: 99%
“…The first step is probably the spontaneous silyltelluration of benzophenone to give 1-siloxy-1-phenylbenzyl phenyl telluride. The second step is radical addition of the resulting telluride to phenyl isonitrile [14]. Subsequent electrolysis of the product gives the corresponding amide in high yield.…”
Section: Hetero-multicomponent Coupling Reactionsmentioning
confidence: 99%
“…We recently found that organotellurium compounds undergo reversible carbon-tellurium bond cleavage upon thermolysis and photolysis, 23,24 and the resulting carbon-centered radicals can react with a variety of radical acceptors. 17,[25][26][27][28][29] During the course of investigating new radical-coupling reactions, we discovered that several organotellurium compounds serve as excellent mediators for living radical polymerization.…”
Section: Introductionmentioning
confidence: 99%